2021
DOI: 10.3390/su131910642
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Use of the Concept of Sustainability in the Romanian Top Universities’ Strategic Plans

Abstract: As the effects of climate change on today’s society make the headlines across the globe, urging all stakeholders to join forces to act and to create a sustainable world, universities have started engaging in the process of building a sustainable future for the generations to come. The sustainable university has thus emerged, a pro-active and collaborative university that performs in several domains. Since the university’s strategic plan is an instance of official and public communication on the future institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The most prominent topics in this field of study have included the implementation of the SDGs, challenges and benefits associated with their application, trends in sustainable development education and promotion strategies. Some studies have sought to identify the obstacles to the effective establishment of sustainable development at universities, finding that higher education institutions still need to do more to integrate sustainability into their curricula and research groups (Leal Filho et al, 2017;Chaleta et al, 2021) and even into their strategic plans (Bieler and McKenzie, 2017;Stoian et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent topics in this field of study have included the implementation of the SDGs, challenges and benefits associated with their application, trends in sustainable development education and promotion strategies. Some studies have sought to identify the obstacles to the effective establishment of sustainable development at universities, finding that higher education institutions still need to do more to integrate sustainability into their curricula and research groups (Leal Filho et al, 2017;Chaleta et al, 2021) and even into their strategic plans (Bieler and McKenzie, 2017;Stoian et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have sought to identify the obstacles to the effective establishment of sustainable development at universities, finding that higher education institutions still need to do more to integrate sustainability into their curricula and research groups (Leal Filho et al , 2017; Chaleta et al , 2021) and even into their strategic plans (Bieler and McKenzie, 2017; Stoian et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this perspective, the concept of a sustainable university emerges (Stoian et al, 2021). In the proposal by Velazquez et al (2006), a sustainable HEI model involves four phases:…”
Section: Incorporation Of Sustainability Into Organizations' Strategi...mentioning
confidence: 99%
“…The mission is a key document of any HEI because it synthesizes its objectives, values and essential activities, constituting a source of inspiration for all of its stakeholders (Fantauzzi et al, 2021). However, several recent studies indicated that, to analyze the real sustainable positioning of an HEI, in addition to verifying the presence of sustainability in mission and policy statements, the content of their respective strategic plans must be evaluated (Di Nauta et al, 2020;S imon et al, 2020;Stoian et al, 2021). Only by reading and analyzing their strategic plans can the intentions declared by the universities be verified as being echoed in practical actions (Stoian et al, 2021).…”
Section: Higher Education Institutionsmentioning
confidence: 99%
See 1 more Smart Citation